Metamorfosis Gerakan Sosial Keagamaan: Antara Polemik, Desiminasi, Ortodoksi, dan Penerimaan terhadap Ideologi Lembaga Dakwah Islam Indonesia (LDII) - Limas Dodi (IAIN Ponorogo, 2017)
Abstract: The Islamic Da'wah Institution of Indonesia (LDII) is connoted as the successor of Islamic Jamaah, thus it is labeled as heretical by certain parties. Even though there are many indications that lead to such perceptions. In fact, LDII is an organization formed by a New Era Government that is assigned to guard the deviation of Islamic teachings by Islamic Jamaah. This paper is intended to analize how far the metamorphosis (in the sense of releasing its past heretic, and its use of new paradigm) of LDII as religious social movement was influenced by Islamic Jamaah, that is between polemics, dissemination, orthodoxy, and the acceptance of its Ideology. Historical and cultural attachments of LDII to Islamic Jamaah lead to other religious groups to still insist on their decision of LDII doctrinal apostasy. The social movement depict that movement emerges and last from various forms and patterns. There are two patterns that influence State-oriented Islamic movement and society-oriented Islamic movement. It appears in two patterns: Everyday life-based and Inward-oriented contemplative movements. The dynamics and strategies of the LDII with government bureaucracies or other religious groups are relationships to position themselves as parallel groups as orthodox groups.الملخص: إن هيئة الدعوة الإسلامية الإندونيسية (LDII) تفهم بأنها الهيئة التي تواصل فكرة